Money Targeting in a Modern Forecasting and Policy Analysis System : an Application to Kenya - Andrle, Michal (IMF Working Papers; Working Paper ;, 2013)
We extend the framework in Andrle and others (2013) to incorporate an explicit role for money targets and target misses in the analysis of monetary policy in low-income countries (LICs), with an application to Kenya. We provide a general specification that can nest various types of money targeting (ranging from targets based on optimal money demand forecasts to those derived from simple money growth rules), interest-rate based frameworks, and intermediate cases. Our framework acknowledges that ex-post adherence to targets is in itself an objective of policy in LICs; here we provide a novel interpretation of target misses in terms of structural shocks (aggregate demand, policy, shocks to money demand, etc). In the case of Kenya, we find that: (i) the setting of money targets is consistent with money demand forecasting, (ii) targets have not played a systematic role in monetary policy, and (iii) target misses mainly reflect shocks to money demand. Simulations of the model under alternative policy specifications show that the stronger the ex-post target adherence, the greater the macroeconomic volatility. Our findings highlight the benefits of a model-based approach to monetary policy analysis in LICs, including in countries with money-targeting frameworks.